Structure of Ego‐Alter Relationships of Politicians in Twitter. Issue 5 (5th September 2017) - Arnaboldi, Valerio; Passarella, Andrea; Conti, Marco; Dunbar, Robin
Abstract : We analyze the ego‐alter Twitter networks of 300 Italian MPs and 18 European leaders, and of about 14, 000 generic users. We find structural properties typical of social environments, meaning that Twitter activity is controlled by constraints that are similar to those shaping conventional social relationships. However, the evolution of ego‐alter ties is very dynamic, which suggests that they are not entirely used for social interaction, but for public signaling and self‐promotion. From this standpoint, the behavior of EU leaders is much more evident, while Italian MPs are in between them and generic users. We find that politicians – more than generic users – create relationships as a side effect of tweeting on discussion topics, rather than by contacting specific alters.